Response to comments on 'Short Note: Extending simplified high-degree synthesis methods to second latitudinal derivatives of geopotential' - Holmes, S.A.; Featherstone, Will (Springer - Verlag, 2014)
We would like to thank Dr. Crouse for taking sufficient interest in our paper so as to correctly and independently detect the typographical error in the initial (un-numbered) equation of Holmes and Featherstone (2002). We also thank him for agreeing to incorporate our own additional corrections into his comment, these being the superfluous modulus symbols that encompass many of the Legendre terms. Our records show these symbols are an unexpected contribution during the typesetting process.We were surprised to see these modulus symbols in the published manuscript, and are now pleased to see them finally identified and dealt with.